ANALISIS KOMPARASI KINERJA KEUANGAN BANK SYARIAH DAN BANK KONVENSIONAL DENGAN PENDEKATAN CAMEL PADA PT BANK BNI SYARIAH, TBK dan PT BANK BNI, TBK PERIODE 2014 â€“ 2018 - Olivia, Monica (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2019)
This study aims to examine the comparison of the financial performance ofÂ  bni syariah banks and conventional bni banks using the CAMEL method, in the period 2014-2018. The method used in this study is a descriptive research method, with a quantitative approach. The type of data used is secondary data, in the form of company financial statements. The test was carried out using the Independent Sample T-Test method using the SPSS 20 program. The results of this study indicate that car and fdr/ldr are not significant differences, but npf/npl, bopo and roa are significant differences between bni syariah banks and conventional bni banks. Keywords : Bank BNI Syariah, Conventional BNI Bank, CAMEL, CAR, FDR/LDR, NPF/NPL/BOPO, ROA